A study of surgical management of idiopathic congenital talipes equinovarus by posteromedial soft tissue release - Parameshwari, T.; Thulasiram, Ketavath; Narender, D.; Kalyani, N.; K, Anjaneyulu (International Journal of Research in Orthopaedics, 2020)
Background: Idiopathic congenital talipes equinovarus is a complex deformity that is difficult to correct. The treatment of club foot is controversial and continues to be one of the biggest challenges in paediatric orthopaedics. Most orthopaedicians agree that the initial treatment should be non-surgical but if it fails, advise surgical treatment in the form soft tissue release for better results. The study was done with the aim to study a short term follow up of 14 patients treated to assess the efficacy of the treatment modality. Methods: 14 patients underwent the posteromedial soft tissue release (PMSTR) at Department of Orthopaedics, S. V. S. Medical College during the period from October 2013 to September 2015. Patients were followed up regularly up to one and half year. Severity of foot deformities were graded according to Denis-Brown classification. Results: Out of 14 cases there were 10 males (71.4%) and 4 females (28.6%) for the sex ratio of 2.5:1 male to female. The youngest child was 6 months old and oldest child was 3 years old. In bilateral cases both feet were operated at an interval of 7 to 10 days. Good results were seen in 15 feet (71%), fair: in 04 feet (19%) and poor: in 02 feet (10%). Conclusions: The PMSTR method is a safe and cost-effective treatment for congenital idiopathic clubfoot and radically decreases the need for extensive corrective surgery. Non-compliance with orthotics after surgery and surgery at late age are causes for failure of technique.